Knowledge, Perceptions and Attitudes of Young Adults Towards Electronic-cigarettes - Mhazo, Pakhani (Department of Public Health and Family Medicine, 2020)
Electronic cigarettes (e-cigarettes) are deemed to be safer than tobacco cigarettes because they do not contain a number of toxicants and carcinogens that are present in tobacco cigarettes. However, their long-term health effects are unknown. Despite concerns surrounding this, there has been a rapid market penetration of e-cigarettes worldwide. South Africa has no legislation which specifically controls the marketing, sale and use of e-cigarettes and concerns have been raised over the increasing use of e-cigarettes by youth, who are often attracted to these novel products. This study is one of the first studies to explore the knowledge and perceptions of ecigarettes in South Africa. A qualitative approach was used to explore young adults’ perceptions, attitudes and behaviour related to e-cigarettes and assess the factors that shape those perceptions. The sources from which the participants accessed e-cigarette-related information were also explored. The study was conducted at the University of Cape Town and participants were registered male and female students at the university. Focus group discussions and individual interviews were used to collect data and thematic analysis approach was used to analyse the data. The results show that participants generally perceived e-cigarettes as healthier than tobacco cigarettes despite showing limited knowledge of the chemical constituents of e-cigarette liquid. Rather, the majority of the participants felt e-cigarettes were safer because of the pleasant smell. A pleasant smell from e-cigarettes was associated with health and the unpleasant smell was associated with danger. E-cigarettes were also viewed as a symbol of social status. The study recommends that e-cigarette awareness should be increased, and e-cigarettes should be regulated as tobacco products to alter the perception that they are safe.